Impact of Friendship Quality on Self-Esteem and Resilience among Adolescents - Tarini Aggarwal; Smriti Sethi (Recent Trends in Social Studies, 2025)
Adolescence is an integral developmental stage of change in social, emotional and psychological aspects of an individual's life. Friendship is an essential component of this period that helps to provide social support and emotional comfort. The present research gaps are not fully addressed by the existing literature on friendship quality, self-esteem, and resilience among adolescents. Hence, the present study sought to establish whether friendship quality and its sub-dimensions of safety, closeness, acceptance and help predict self-esteem and resilience. A quantitative, correlational research design was employed, and the participants were 80 adolescents (40 males and 40 females) 13 to 19 years of age, randomly selected. The variables were measured by Friendship Quality Scale by Thien et al. (2012), the Rosenberg Self-Esteem Scale (Rosenberg, 2006), and the Brief Resilience Scale by Smith et al. (2008). Descriptive statistics, indicated no significant gender differences in friendship quality, self-esteem, or resilience. Correlation analysis did not reveal any significant relationship between the overall friendship quality and self-esteem or resilience. Very low and insignificant correlations were observed with self-esteem for closeness and help, while acceptance had the highest correlation with resilience. Regression analysis also supported the fact that friendship quality and its domains failed to predict self-esteem and resilience significantly. The study concluded that friendship quality is not a primary determinant of self-esteem or resilience in adolescents which suggests that personal achievements, coping mechanisms and family environment may play a more crucial role. These findings further highlight the need for broader social support systems and interventions beyond peer relationships to foster adolescent well-being. Future research should explore longitudinal approaches and additional psychological factors contributing to self-esteem and resilience.
Keywords: Adolescents; Friendship Quality; gender differences; resilience; self-esteem